Do all adult orthopaedic injuries seen in emergency departments need to attend fracture clinic? A Queensland multicentred review. (1st June 2017) - Cleary, Aidan; Zeller, Robert; Maguire, Chris; Goh, Shyan; Shortt, Nick
Abstract: Objective: Musculoskeletal injuries account for a significant proportion of ED presentations annually, with a large percentage being referred to the fracture clinic (FC). A literature review found that many referrals could be safely managed outside the traditional model of care. The present study aims to review all adult presentations to FCs at two Queensland metropolitan hospitals, finding low‐risk injuries that can safely and appropriately be managed by their general practitioner (GP) or allied health professionals (AHPs), potentially affording significant savings to the health system. Methods: A retrospective study at Logan and Redland Hospitals was undertaken, reviewing all adult patients (≥16 years) referred to FCs over an eight week period. Injuries were categorised into those requiring FC care supervised by an orthopaedic surgeon (fracture clinic pathway) and those that could be safely managed by GPs or AHPs, with the aid of evidence‐based, protocol‐driven guidelines known as the primary care pathway (PCP). Results: A total of 1367 patients were referred to FC over the study period, of whom 546 (40%) were assessed as suitable candidates for PCP. Redland Hospital accounted for 65% of all PCP‐suitable patients, whereas Logan Hospital accounted for 35%. Failure‐to‐attend rates were significantly higher ( P < 0.001) in the PCP patients compared to other patients attending FCs. Conclusion: Adopting the PCP could potentially reduce fracture clinic referrals by 40%. Having a structured pathway has the potential to empower primary health professionals, which could result in a more streamlined process that aids in significant time and financial savings and maintains good patient satisfaction and outcomes.